Kinetic and Thermodynamic Stabilization of Metal Complexes by Introverted Coordination in a Calix[6]azacryptand. Issue 14 (24th February 2016) - Inthasot, Alex; Brunetti, Emilio; Lejeune, Manuel; Menard, Nicolas; Prangé, Thierry; Fusaro, Luca; Bruylants, Gilles; Reinaud, Olivia; Luhmer, Michel; Jabin, Ivan; Colasson, Benoit
Abstract: The Huisgen thermal reaction between an organic azide and an acetylene was employed for the selective monofunctionalization of a X6 ‐azacryptand ligand bearing a tren coordinating unit [X6 stands for calix[6]arene and tren for tris(2‐aminoethyl)amine]. Supramolecular assistance, originating from the formation of a host–guest inclusion complex between the reactants, greatly accelerates the reaction while self‐inhibition affords a remarkable selectivity. The new ligand possesses a single amino‐leg appended at the large rim of the calixarene core and the corresponding Zn 2+ complex was characterized both in solution and in the solid state. The coordination of Zn 2+ not only involves the tren cap but also the introverted amino‐leg, which locks the metal ion in the cavity. Compared with the parent ligand deprived of the amino‐leg, the affinity of the new monofunctionalized X6 tren ligand 6 for Zn 2+ is found to have a 10‐fold increase in DMSO, which is a very competitive solvent, and with an enhancement of at least three orders of magnitude in CDCl3 /CD3 OD (1:1, v/v). In strong contrast with the fast binding kinetics, decoordination of Zn 2+ as well as transmetallation appeared to be very slow processes. The monofunctionalized X6 tren ligand 6 fully protects the metal ion from the external medium thanks to the combination of a cavity and a closed coordination sphere, leading to greater thermodynamic and kinetic stabilities. Abstract : Introverted guest : A calix[6]arene‐based azacryptand ligand bearing one additional amino‐leg was selectively synthesized. Upon cation binding, this amino‐leg occupies the cavity of the calixarene core. Such a coordination mode was fully characterized in solution and in the solid state for the Zn II complex. The introverted coordination of the amino‐leg allows for higher kinetic and thermodynamic stabilities (see figure).